PENGGUNAAN MODEL PIMCA BERBASIS MULTIREPRESENTASI DALAM PEMBELAJARAN FISIKA MATERI SUHU DAN KALOR - Roring, Magda Silviani; Londa, Treesje Katrina; Mongan, Satyano (Charm Sains: Jurnal Pendidikan Fisika, 2024)
Strategies to improve student learning outcomes that need to be planned by teachers, for example using appropriate learning models. The PIMCA model is one of the new learning models that can be used to improve the skills of understanding physics concepts. The PIMCA model consists of four stages: Presentation, Idea Mapping, Conceptualization and Formative Assessment. This study aims to determine the average increase in students' cognitive learning outcomes through the application of the Multi-representation-based PIMCA learning model in physics learning on temperature and heat material. The type of research used is pre-experimental research with the One Group Pretest-Posttest Design method. This research was conducted at SMA Negeri 2 Tondano in the even semester of the 2021/2022 academic year. The subjects in this study were students of class XI IPA SMA Negeri 2 Tondano, totaling 30 students. The instrument used is a multi-representation-based test instrument in the form of multiple choice questions. The data analysis technique used descriptive statistical analysis and normalized gain test (N-gain). The results of data analysis obtained the average value of the pretest was 29.7 and the average value of the posttest was 74.93. The results of the N-gain test showed that there were 19 students who experienced an increase in learning outcomes in the medium N-gain category and 11 students in the high N-gain category. The results of this study indicate that the Multirepresentation-based PIMCA learning model can improve understanding of the concepts of temperature and heat and can improve student learning outcomes.).